2014
DOI: 10.1371/journal.pone.0096931
|View full text |Cite
|
Sign up to set email alerts
|

Directed Evolution of Improved Zinc Finger Methyltransferases

Abstract: The ability to target DNA methylation toward a single, user-designated CpG site in vivo may have wide applicability for basic biological and biomedical research. A tool for targeting methylation toward single sites could be used to study the effects of individual methylation events on transcription, protein recruitment to DNA, and the dynamics of such epigenetic alterations. Although various tools for directing methylation to promoters exist, none offers the ability to localize methylation solely to a single C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 49 publications
(59 reference statements)
1
30
0
Order By: Relevance
“…Methylation of only a single site in a target DNA was selected for by digesting with a target site-specific restriction endonuclease and a second, unusual restriction enzyme that digests DNA with two distally methylated sites [27]. This method identified methyltransferase variants that showed 80% methylation at the target site and less than 1% methylation at off-target sites.…”
Section: Advancing Selection Technologiesmentioning
confidence: 99%
“…Methylation of only a single site in a target DNA was selected for by digesting with a target site-specific restriction endonuclease and a second, unusual restriction enzyme that digests DNA with two distally methylated sites [27]. This method identified methyltransferase variants that showed 80% methylation at the target site and less than 1% methylation at off-target sites.…”
Section: Advancing Selection Technologiesmentioning
confidence: 99%
“…For example, one group of investigators has reported the development of an interesting technology for promoting genomic locus-specific DNA methylation, using 2 different ZFs designed to bind to DNA flanking a target CpG site that are each fused with a component of a bifurcated DNA methyltransferase [115][116][117]. This approach aims to increase the local concentration of both methyltransferase fragments when the ZFs bind to the genome, leading to the assembly of an active methyltransferase enzyme only at the target site.…”
Section: Synthetic Biologymentioning
confidence: 99%
“…The regulation of methylation could be achieved either by 1) site-specific methylation or by 2) sitespecific demethylation of target genes. Engineered zinc fingermethyltransferase domains have been shown promises for site-specific methylation to a hypomethylated region of genome [20,21]. Similarly engineered TDG could offer site-specific demethylation of target genes which are hypermethylated.…”
Section: Editorialmentioning
confidence: 99%